2020
DOI: 10.1519/jsc.0000000000003626
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Responses During a Cycling Test to Exhaustion While Wearing the Elevation Training Mask

Abstract: L ópez-P érez, ME, Romero-Arenas, S, Colomer-Poveda, D, Keller, M, and M árquez, G. Psychophysiological responses during a cycling test to exhaustion while wearing the elevation training mask. J Strength Cond Res 36(5): 1282-1289, 2022-The aim of this study was to investigate the psychophysiological effects of wearing the elevation training mask (ETM). Twelve men performed time-toexhaustion (TTE) tests at 75% of peak power output with and without wearing the ETM. Heart rate (HR), rating of perceived exertion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Considering that mask wearing may cause discomfort and this could compromise the exercise performance parameters ( Motoyama et al, 2016 ; Andre et al, 2018 ; Fikenzer et al, 2020 ; López-Pérez et al, 2020 ; Tornero-Aguilera et al, 2021 ; Boyle et al, 2022 ), the acute effects of face mask use were investigated through different exercise performance aspects. Previous systematic reviews ( Engeroff et al, 2021 ; Shaw et al, 2021 ) showed no effects of face mask wearing on exercise performance.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that mask wearing may cause discomfort and this could compromise the exercise performance parameters ( Motoyama et al, 2016 ; Andre et al, 2018 ; Fikenzer et al, 2020 ; López-Pérez et al, 2020 ; Tornero-Aguilera et al, 2021 ; Boyle et al, 2022 ), the acute effects of face mask use were investigated through different exercise performance aspects. Previous systematic reviews ( Engeroff et al, 2021 ; Shaw et al, 2021 ) showed no effects of face mask wearing on exercise performance.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that mask wearing may cause discomfort and this could compromise the exercise performance parameters (Motoyama et al, 2016;Andre et al, 2018;Fikenzer et al, 2020;López-Pérez et al, 2020;Tornero-Aguilera et al, 2021;Boyle et al, 2022), the acute effects of face mask use were investigated through different exercise performance aspects. Previous systematic reviews (Engeroff et al, 2021; showed no effects of face mask wearing on exercise performance.…”
Section: Discussionmentioning
confidence: 99%